Design of Single Phase Inverter With Pulse Width Modulation Control System Using Fast PWM - Kurniawan, Aditya Dwi; Radianto, Donny; Luqman, Mohammad (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2024)
The increase in electricity consumption in Indonesia can increase the possibility of disruption to the electricity network system that is used as a source of AC voltage for the community. To overcome these disturbances, PT. PLN will cut off the electricity network and then carry out repairs at points where disturbances are detected. The process of disconnecting the electricity network can disrupt community activities. Advances in power electronics technology and science have produced a solution in the form of a device that can convert DC electricity to AC. The tool is an inverter. Researchers will design a full-bridge topology single-phase inverter with a 12 VDC voltage source. The microcontroller used to control the switching of the full bridge circuit and maintain voltage stability with AC voltage feedback is Arduino Uno. The output voltage of the inverter will be increased to 220 Volts using a transformer. PWM signal generation with Fast PWM mode is used to generate sinusoidal signals with a frequency of 50 Hz and reduce harmonic distortion at the output of the inverter. This thesis will make a single-phase inverter with AC output voltage feedback and it is hoped that the method used can produce an inverter with small harmonic distortion with a stable output voltage.